2022
DOI: 10.1002/smr.2485
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analysis of software development in cloud computing perceptions

Abstract: Cloud computing is characterized as a shared computing and communication infrastructure. It encourages the efficient and effective developmental processes that are carried out in various organizations. Cloud computing offers both possibilities and solutions of problems for outsourcing and management of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 101 publications
0
2
0
Order By: Relevance
“…The paper highlights the need for more empirical studies in this research area. [19] It aims to review and analyze the literature on cloud-based learning adoption in educational institutions and identify the most frequent factors affecting its adoption. The study found 32 suitable articles from sources such as Science Direct, Emerald, and IEEE and identified ease of use, usefulness, and security as the most frequent factors.…”
Section: B Implementing E-learning-based Cloud Computing Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…The paper highlights the need for more empirical studies in this research area. [19] It aims to review and analyze the literature on cloud-based learning adoption in educational institutions and identify the most frequent factors affecting its adoption. The study found 32 suitable articles from sources such as Science Direct, Emerald, and IEEE and identified ease of use, usefulness, and security as the most frequent factors.…”
Section: B Implementing E-learning-based Cloud Computing Challengesmentioning
confidence: 99%
“…We have developed unique strings for each digital library as the string formation guidelines of different libraries vary. In this process, we followed the recent study [19], which aimed to analyze software development practices in cloud computing systematically. This research explores perceptions and insights about the software development process within cloud computing environments.…”
Section: ) Study Selection Criteriamentioning
confidence: 99%